2000
DOI: 10.1007/s002210000497
|View full text |Cite
|
Sign up to set email alerts
|

The role of the lateral parabrachial nuclei in concurrent and sequential taste aversion learning in rats

Abstract: The purpose of this study was to examine the role of the external lateral parabrachial subnucleus (PBNLe) in two different taste aversion learning (TAL) procedures. For the first, short-term (concurrent) TAL, two different-flavored stimuli were presented at the same time, one associated with simultaneous intragastric administration of an aversive product, hypertonic NaCl, and the other with saline. In the second, long-term (sequential/delayed) TAL, each gustatory stimulus was presented every other day and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
6
15
0
Order By: Relevance
“…The present findings also confirm that tiapride administration impairs the place aversion induced by NLPBe electrical stimulation (Hurtado et al 2014), while the utilization of a higher tiapride dose (40 mg/kg) allowed a dose-response curve to be constructed, suggesting a DA-receptor drug window for the aversive behavior rather than adverse associated heterogeneous actions, which would also have been observed in the positive group, which was not the case. These data are consistent with previous observations by our group that the NLPBe forms part of a brain pathway underlying concurrent taste learning (Mediavilla et al 2000(Mediavilla et al , 2005. Thus, specific lesions of this subnucleus were found to impair the acquisition of concurrent taste aversions (Mediavilla et al 2000(Mediavilla et al , 2011, an implicit learning modality that is also interrupted by tiapride administration (Mediavilla et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present findings also confirm that tiapride administration impairs the place aversion induced by NLPBe electrical stimulation (Hurtado et al 2014), while the utilization of a higher tiapride dose (40 mg/kg) allowed a dose-response curve to be constructed, suggesting a DA-receptor drug window for the aversive behavior rather than adverse associated heterogeneous actions, which would also have been observed in the positive group, which was not the case. These data are consistent with previous observations by our group that the NLPBe forms part of a brain pathway underlying concurrent taste learning (Mediavilla et al 2000(Mediavilla et al , 2005. Thus, specific lesions of this subnucleus were found to impair the acquisition of concurrent taste aversions (Mediavilla et al 2000(Mediavilla et al , 2011, an implicit learning modality that is also interrupted by tiapride administration (Mediavilla et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with previous observations by our group that the NLPBe forms part of a brain pathway underlying concurrent taste learning (Mediavilla et al 2000(Mediavilla et al , 2005. Thus, specific lesions of this subnucleus were found to impair the acquisition of concurrent taste aversions (Mediavilla et al 2000(Mediavilla et al , 2011, an implicit learning modality that is also interrupted by tiapride administration (Mediavilla et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data support the proposal of two different mechanisms that explain the consequences of intragastrically administered nutrients (Agü ero et al 1993a,b;Mediavilla et al 2000Mediavilla et al , 2005. One is independent of the LPB, given that the lesioned animals and controls both show aversion to the intragastrically administered nutrients by rejecting the associated gustatory stimulus.…”
Section: Discussionsupporting
confidence: 88%
“…The vagus nerve-NSTic-LPBe pathway also proved essential for the rapid transmission of nonnutritional visceral information. We found that the vagus nerve [83] and NSTic [139] or LPBe [140] are necessary for concurrent taste aversion learning but not for sequential TAL.…”
Section: Transmission Pathways Of Rewarding Visceral Information To Tmentioning
confidence: 74%